School absence in the United States: understanding the role of STEM-related vocational education and training in encouraging attendance. (2nd October 2022) - Plasman, Jay Stratte; Gottfried, Michael A.
ABSTRACT: Recent federal education policies and initiatives in the United States have emphasised the importance of college and career readiness and showing up in school. The Carl D. Perkins Career and Technical Education Improvement Act provides federal funding for career and technical education (CTE) in the country, and key pieces of the act focus on increasing participation in career training coursework related to high demand and high paying careers, with a specific emphasis on maths and science fields. Additionally, the act highlights the need to increase participation in CTE work for 'special populations' – including low-income and under-represented minority (URM) students. With regards to attendance, the Every Student Succeeds Act (ESSA) allowed for states to individually decide upon a less traditional measure of school success. In response, 36 states identified chronic absence as that measure. Using an instrumental variable estimation approach, we explore the relationship between applied STEM career and technical education (AS-CTE) and absence from school. We explore this relationship broadly, as well as for low-income and URM students more specifically. We find that participation in AS-CTE is predictive of fewer absences as well as reduced probability of excessive absences. Implications are discussed.